The Alpha Programme: Some Tentative Observations of State of the Art Evangelism in the UK - Hunt, Stephen (Journal of contemporary religion, 2003)
The Alpha programme is a highly publicised and innovative evangelising campaign that has been endorsed by tens of thousands of churches worldwide. Based around a ten-week introductory course in Christianity, it is designed to provide a 'safe' environment for those enquiring into the faith. Practically all church traditions and denominations have praised the value of Alpha and have come to accept it widely as almost the last word in contemporary evangelism. Alpha also provides a barometer of Christianity today. This paper, based on research in the UK, seeks to explore the way in which Alpha has attempted to establish a bridge between Christianity and secular culture for the purposes of evangelism, considers the implications of the global exportation of a commercial 'package', and seeks to answer the question whether the programme provides a realistic means of reversing church decline.